2011
DOI: 10.1080/09583157.2011.568112
|View full text |Cite
|
Sign up to set email alerts
|

Can cruciferous agroecosystems grown under variable conditions influence biological control ofPlutella xylostella(Lepidoptera: Plutellidae)?

Abstract: Determining the most efficacious method for the release of parasitoids is challenging, depending on the crop area to be covered and the environmental conditions created by the agroecosystem. Release of the parasitoid Oomyzus sokolowskii (Kurdjumov) and the effect of crucifers cropping systems were investigated in relation to diamondback moth (DBM), Plutella xylostella (L.) control. First, we investigated the dispersal ability of O. sokolowskii. Kale plants were infested with 20, 25, 30 and 35 DBM larvae each, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
1
9
0
1
Order By: Relevance
“…Generally, moths do not oviposit on non-host plants; their host acceptance and oviposition is associated with a complicated integrated suite of chemical and physical cues [86]. Therefore, where soft insecticides are utilised, crop systems approached through the modification of agro-ecosystems and cropping practices can also be manipulated to confuse the adults' host finding techniques [88]. Research has Figure 5.…”
Section: Possible Novel Dbm Control Optionsmentioning
confidence: 99%
“…Generally, moths do not oviposit on non-host plants; their host acceptance and oviposition is associated with a complicated integrated suite of chemical and physical cues [86]. Therefore, where soft insecticides are utilised, crop systems approached through the modification of agro-ecosystems and cropping practices can also be manipulated to confuse the adults' host finding techniques [88]. Research has Figure 5.…”
Section: Possible Novel Dbm Control Optionsmentioning
confidence: 99%
“…Research has shown partial DBM repellence success of cabbage intercrops with alliums through confusion in the chemical cues [12,78,79]. In such intercrops, natural enemies were shown to disperse and parasitise DBM at similar rates as in monocrops [88], evidence of compatibility between natural enemies and a cropping systems approach. There is potential in further improving this concept into a 'push-pull' cropping system technology by selecting appropriate repellent and attractant crops.…”
Section: Possible Novel Dbm Control Optionsmentioning
confidence: 95%
“…Generally, moths do not oviposit on non-host plants; their host acceptance and oviposition is associated with a complicated integrated suite of chemical and physical cues [86]. Therefore, where soft insecticides are utilised, crop systems approached through the modification of agro-ecosystems and cropping practices can also be manipulated to confuse the adults' host finding techniques [88]. Research has shown partial DBM repellence success of cabbage intercrops with alliums through confusion in the chemical cues [12,78,79].…”
Section: Possible Novel Dbm Control Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian mereka juga menunjukkan bahwa penanaman sawi (famili Brassicaceae) yang diseling dengan tumbuhan famili non-Brassicaceae menarik lebih banyak predator dan parasitoid yang menyebabkan jumlah kematian lebih tinggi pada larva Plutella xylostella dan Pieris rapae, hama utama tanaman Brassicaceae, dibandingkan dengan plot yang hanya ditanami sawi. Agroekosistem tanaman Brassicaceae (krusifer, kubisan) yang dibudidayakan melalui penganekaragaman jenis tanaman di sekelilingnya, ternyata mampu memperkuat usaha pengendalian hayati ulat daun kubis Plutella xylostella menggunakan parasitoid Oomipus sokolowski (Silva Torres et al, 2011). Dalam hal ini, keragaman vegetasi meningkatkan keragaman spesies musuh alami yang berpotensi menekan populasi organisme pengganggu tanaman seperti juga ditunjukkan oleh Straub dan Snyder (2008) pada pertanaman sawi dan kentang.…”
Section: Sistem Pertanian Berbasis Konservasi Musuh Alamiunclassified